Model Problem Based Learning Terintegrasi TPACK Terhadap Kemampuan Literasi Numerasi Siswa - Pebrianti, Vitriya Asih; Samijo; Sulistyono, Bambang Agus (Polinomial : Jurnal Pendidikan Matematika, 2025)
The low mastery of students' numeracy literacy has become a serious problem in mathematics education, requiring effective learning innovations to bridge the gap between the needs of 21st-century numeracy competencies and students' actual achievements, which are still low. This study aims to analyze the effect of the problem-based learning model integrated with TPACK on students' numeracy literacy skills. This study used a quantitative approach with a quasi-experimental design, specifically the pretest-posttest control group design. The population in this study consisted of eighth-grade students at SMP Negeri 1 Pagu. The research sample was selected using random sampling technique from the population. This study used research instruments in the form of numeracy literacy tests, as well as data collection techniques through pre-tests and post-tests. Data analysis was performed using statistical data analysis and the Independent Sample t-Test. The results of the study, with a significance value of the t-test of 0.000 < 0.05, indicate that the application of the problem-based learning model integrated with TPACK has a significant effect on students' numeracy literacy skills. The average N-Gain of the experimental class was 0.76, categorized as high, while the control class was 0.49, categorized as moderate.